Analisis Dan Perancangan Website SMKN 13 Bandung - Imannudin Akbar (NUANSA INFORMATIKA, 2024)
Information and communication technology plays an important role in supporting and increasing efficiency in managing daily activities, as well as enabling work to be done from anywhere. 13 Bandung Vocational High School is a secondary level school in the city of Bandung which has competency expertise in the fields of Chemical Analysis, Computer Network Engineering and Software Engineering. 13 Bandung Vocational High School needs a website as a school media for conveying information about school activities and as a media for promoting the school to the general public so that people know more about SMKN 13 Bandung. The system development method uses the prototype development method. Prototyping is the creation of an accurate testing system. Through a prototype, managers can get an overview and ideas regarding the application design requirements. The results of this research are to provide the results of the analysis and provide the results of designing the 13 Bandung Vocational High School website with the hope that this website design can be used for the implementation process of creating the 13 Bandung Vocational High School website